2012
DOI: 10.1017/s0031182011002320
|View full text |Cite
|
Sign up to set email alerts
|

Blood feeding in juvenileParagnathia formica(Isopoda: Gnathiidae): biochemical characterization of trypsin inhibitors, detection of anticoagulants, and molecular identification of fish hosts

Abstract: The 3 post-marsupial juvenile stages of the gnathiid isopod, Paragnathia formica, are haematophagous ectoparasites of fishes that may, in heavy infestations, cause host mortality. Protein digestion in fed stage 3 juveniles is accomplished by cysteine proteinases, but what bioactive compounds attenuate host haemostatic, inflammatory and immunological responses during feeding is unknown. Trypsin inhibitory activity and anticoagulant activity were detected in crude extracts of unfed P. formica stage 1 juveniles; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…It is well known that blood-feeding parasites, such as ticks, mosquitoes, fleas and leeches need to evade the clotting system of their vertebrate hosts and maintain blood flow during feeding [34, 35]. Many researchers consider that isopod parasites may inject anticoagulants or other compounds directly into the blood to obtain their “blood meal” [11, 31]. In order to suck the hemolymph, T. chinensis may secrete various anticoagulants, which could work cooperatively and prevent blood clotting by downregulating the expression of clotting-related proteins at the site of injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that blood-feeding parasites, such as ticks, mosquitoes, fleas and leeches need to evade the clotting system of their vertebrate hosts and maintain blood flow during feeding [34, 35]. Many researchers consider that isopod parasites may inject anticoagulants or other compounds directly into the blood to obtain their “blood meal” [11, 31]. In order to suck the hemolymph, T. chinensis may secrete various anticoagulants, which could work cooperatively and prevent blood clotting by downregulating the expression of clotting-related proteins at the site of injury.…”
Section: Discussionmentioning
confidence: 99%
“…Ectoparasitic isopods feed primarily on blood (hemolymph) that oozes from wounds of the host after the integument has been perforated by the isopod’s mandibles, which can cause host stress, tissue damage, secondary infection and mortality [1, 810]. Although trypsin inhibitors and anticoagulants have been found in isopod parasites, the mechanism by which it evades the immune response of the host during parasitism is still unclear; Manship et al [11] proposed that the mechanism may include hemostasis, which limits blood loss by vasoconstriction and platelet aggregation. This is similar to the mechanism used by ticks [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although parasitism is a common lifestyle for isopods, almost nothing is known about the potential role played by bioactive molecules. An exception is a recent study on gnathiid isopods ( Paragnathia formica ), the juveniles of which are hematophagous ectoparasites of fish [ 68 ]. This study showed that crude extracts of juveniles have trypsin inhibitory and anticoagulant activities.…”
Section: Arthropodamentioning
confidence: 99%
“…Isopod parasites mainly feed on blood (hemolymph) from hosts after perforating the integument with their mandibles, which can cause stress, tissue damage, secondary infection, and mortality (Wilson, 2008; Poore and Bruce, 2012; Williams and Boyko, 2012; Smit et al, 2014). There is evidence that isopod parasites may also inject anticoagulants or other compounds directly into the host so as to evade defensive responses (Nair and Nair, 1983; Manship et al, 2012). At present, only a few proteins for this purpose have been identified, including trypsin inhibitors and anticoagulants in Paragnathia formica .…”
Section: Introductionmentioning
confidence: 99%